A dysfunctional endolysosomal pathway common to two sub-types of demyelinating Charcot–Marie–Tooth disease - James R. Edgar; Anita K. Ho; Matilde Laurá; Rita Horvath; Mary M. Reilly; J. Paul Luzio; Rhys C. Roberts (Acta Neuropathologica Communications, 2020)
Abstract Autosomal dominant mutations in LITAF are responsible for the rare demyelinating peripheral neuropathy, Charcot–Marie–Tooth disease type 1C (CMT1C). The LITAF protein is expressed in many human cell types and we have investigated the consequences of two different LITAF mutations in primary fibroblasts from CMT1C patients using confocal and electron microscopy. We observed the appearance of vacuolation/enlargement of late endocytic compartments (late endosomes and lysosomes). This vacuolation was also observed after knocking out LITAF from either control human fibroblasts or from the CMT1C patient-derived cells, consistent with it being the result of loss-of-function mutations in the CMT1C fibroblasts. The vacuolation was similar to that previously observed in fibroblasts from CMT4J patients, which have autosomal recessive mutations in FIG4. The FIG4 protein is a component of a phosphoinositide kinase complex that synthesises phosphatidylinositol 3,5-bisphosphate on the limiting membrane of late endosomes. Phosphatidylinositol 3,5-bisphosphate activates the release of lysosomal Ca2+ through the cation channel TRPML1, which is required to maintain the homeostasis of endosomes and lysosomes in mammalian cells. We observed that a small molecule activator of TRPML1, ML-SA1, was able to rescue the vacuolation phenotype of LITAF knockout, FIG4 knockout and CMT1C patient fibroblasts. Our data describe the first cellular phenotype common to two different subtypes of demyelinating CMT and are consistent with LITAF and FIG4 functioning on a common endolysosomal pathway that is required to maintain the homeostasis of late endosomes and lysosomes. Although our experiments were on human fibroblasts, they have implications for our understanding of the molecular pathogenesis and approaches to therapy in two subtypes of demyelinating Charcot–Marie–Tooth disease.